Density indices for forest stands Simarouba amara Aubl - Mojena, P. A. (Scientific Electronic Archives, 2017)
Â The study aimed to develop indices of density stands Simarouba amaraÂ Â based Crown Competition Factor, index do stand of Reineke and Yoda as density measurements. The data used come from dendrometric 12 variables fixed area plots and age 15 installed in the region of Sinop-MT. Calculated by the Crown Competition Factor 105 value indicates high competition among the trees. The maximum size guide density ratio considering the method of ordinary least squares regression defined with a regression coefficient of -1.9088 an index of 422 trees per hectare based on the average diameter of 25 to quadratic model Reineke, Yoda for the model with a regression coefficient of 0.9937 and with reference to 100 trees volume was 2.43 cubic meters per hectare. Management diagrams density for the species produced using the mean quadratic diameter, number of trees per hectare Volume and showed a good efficiency to estimate the density indexes that could be used in the management of the species in the region.